Some evidence about the physiological basis of flesh reddening symptoms in plum fruit - Vicente, Ariel Roberto; Crisosto, Carlos H.; Manganaris, George A. (My University, 2010)
Flesh reddening has been described as one of the manifestations of chilling injury (CI) symptoms in stone fruits, including plum, peach and nectarine fruit. Flesh reddening in peach and nectarine fruit is most evident around the pit cavity, while symptoms in plum appear initially as discoloration in the fruit flesh periphery that later is extended towards the pit cavity, covering the whole mesocarp. Intriguingly, ethylene has different effects on the incidence of flesh reddening symptoms in these phenotypically related, yet distinct species. While it is exacerbated in plums stored at 5°C under continuous ethylene exposure and is significantly reduced by 1-methylcyclopropene (1-MCP) treatments, in nectarines the opposite is true. This review study indicates that the nature of flesh reddening differs among stone fruits and suggests that in the case of plum ethylene synthesis is not merely an additional consequence of CI symptoms, it is important for the development of the disorder. Finally, the fact that flesh reddening has been observed in non-refrigerated plums during ripening after harvest suggests that flesh reddening in this fruit should be considered a general response to the stresses associated with postharvest storage and not only a CI disorder
Keywords: Cold storage; Ethylene; Fruit--Quality; Plum; Peach